Cryobacterium soli sp. nov., isolated from forest soil. Issue 1 (3rd February 2020) - Gong, Chunjie; Lai, Qiliang; Cai, Hanfeng; Jiang, Yanming; Liao, Hu; Liu, Yunfei; Xue, Dongsheng
Abstract : A taxonomic study was performed on strain GCJ02 T, which was isolated from forest soil from Baishan City, PR China. The bacterium was Gram-stain-positive, catalase-positive and weakly oxidase-positive, rod-shaped and non-motile. Growth was observed at salinities of 0–6.0 % and at temperatures of 4–26 °C. Phylogenetic analysis based on 16S rRNA gene sequences indicated that GCJ02 T represented a member of the genus Cryobacterium, with the highest sequence similarity to Cryobacterium arcticum SK1 T (99.5 %) and Cryobacterium zongtaii TMN-42 T (99.5 %), followed by Cryobacterium psychrotolerans CGMCC 1.5382 T (97.7 %), and other species of the genus Cryobacterium (96.4–96.9 %). The ANI and the DNA–DNA hybridization estimate values between GCJ02 T and all type strains of species of the genus Cryobacterium were 72.5–84.5 % and 19.6–28.7 %, respectively. The principal fatty acids (>10 %) of GCJ02 T were anteiso-C15 : 0 (53.0 %) and anteiso-C17 : 0 (18.8 %). The G+C content of the chromosomal DNA was 68.4 mol%. The respiratory quinone was determined to be MK-10. Phosphatidylglycerol, diphosphatidylglycerol, glycolipid, and one unidentified phospholipid and three unidentified polar lipid were present. The combined genotypic and phenotypic data indicated that strain GCJ02 T represents a novel species within the genus Cryobacterium, for which the name Cryobacterium soli sp. nov. is proposed, with the type strain GCJ02 T (=MCCC 1K03549 T =JCM 32391 T ).